Physical, Mechanical and Durability Study of Dunes Sand Mortar in the Region of Laghouat - Lakhdar Azzouz; Benchaa Benabed; Akram Salah Eddine Belaidi (The Minerals, Metals and Materials Society, 2008)
"The dunes sand is a material of a large availability in Algeria. This material is practically unexploited. The introduction of this material as a new element in the construction can be more relieve the domain of building, and contribute to the development of the southern regions of Algeria, which are very rich in this material. The main objective of our work is to exploit a largely available material in the Algerian south which is the dunes sand, as a material of construction in the region of Laghouat.In this study, first we investigated the effect of the curing environment and the nature of the sand on the mechanical properties of the mortar, such as; flexural and compressive strengths. Then after, we studied the durability of the mortar under cycles of wettingdrying and the chemical attack of sodium sulfate (Na2SO4 5%).According to the results, we note that the mortar of the sand mixes (river sand plus dunes sand) present the best mechanical performances under different environment of curing. In addition result of durability studies put forward that the mortar of the sand mixes is more resistant to the sulfates attack."